Literature Review on the Value of Piety in Strengthening Work Ethic - Bina Prima Panggayuh; Annur Hafifah El Firdausy; Nasywa Nabilla Hakim; Najwa Syarifah; Siti Salwa (Aslama: Journal of Islamic Studies, 2025)
This study discusses the influence of taqwa values in strengthening work ethic using a literature review method. Taqwa values are spiritual and moral principles that form the basis of a Muslim's behavior in daily life, especially in the aspect of work. Using the literature review method, this study collected various references such as the Qur'an, Hadith, major classical works, and contemporary literature on work ethics. The value of taqwa serves as a spiritual foundation that shapes moral awareness, discipline, and integrity in a person. When this value is instilled, it manifests in a stronger work ethic, characterized by intrinsic motivation, professionalism, and dedication to quality and responsibility. The work ethic built from these spiritual values then plays a direct role in improving performance, as individuals work with greater focus, responsibility, and maintain high ethical standards. Therefore, this conceptual model emphasizes that strengthening taqwa is an important element in creating a professional work ethic, which ultimately improves the effectiveness and quality of performance in the modern workplace.